Self-enforcing agreements on water allocation - Erik Ansink (Fondazione Eni Enrico Mattei (FEEM), 2009)
Many water allocation agreements in transboundary river basins are inherently unstable. Due to stochastic river flow, agreements may be broken in case of drought. The objective of this paper is to analyse whether water allocation agreements can be self-enforcing. An agreement is modelled as the outcome of bargaining game on river water allocation. Given this agreement, the bargaining game is followed by a repeated extensive-form game in which countries decide whether or not to comply with the agreement. I assess under what conditions such agreements are self-enforcing, given stochastic river flow. The results show that, for sufficiently low discounting, every efficient agreement can be sustained in subgame perfect equilibrium. Requiring renegotiation-proofness may shrink the set of possible agreements to a unique self-enforcing agreement. The solution induced by this particular agreement implements the downstream incremental distribution, an axiomatic solution to water allocation that assigns all gains from cooperation to downstream countries.
Keywords: C73; Q25; 330; Self-Enforcing Agreement; Repeated Extensive-Form Game; Water Allocation; Renegotiation-Proofness